Representation of Women Leadership in Nussa and Rara Animation from the Question of Representation Perspective - Lisnawati, Lisnawati; Praptiningsih, Novi Andayani; Heryanto, Gun Gun; Bakti, Andi Faisal; Hayat, Heni (Institut Komunikasi dan Bisnis LSPR, 2024)
This research examines gender representation in the animated series Nussa and Rara. It applies Gill Branston and Roy Stafford's